2018
DOI: 10.2136/sssaj2017.04.0125
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Solute Transport in Cemented Porous Media: Pore‐scale Simulations

Abstract: The porous media with higher cementation degree have wider velocity spreads. The solute transport becomes more anomalous with increasing cementation degree. It is the changing characteristics of the flow field that lead to more anomalous solute transport. The pore structure of porous media varies significantly with the change in the degree of cementation among solid grains, and recent studies have shown that pore structure greatly influences anomalous solute transport. Nevertheless, limited effort has been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…It has been observed that in many cases, two-dimensional simulation schemes can grasp the majority of the physical processes of solute transport and reduce the simulation complexity and calculation costs, compared with threedimensional simulations. In addition, in the previous study, we found that when the cementation degree increases, the velocity probability distribution of fluid in 2D media and 3D media and its change trend are similar [28,29]. Therefore, this study performed two-dimensional simulations at the pore scale for the purpose of exploring the solute dilution processes in porous media with different cementation degrees.…”
Section: Methodsmentioning
confidence: 89%
“…It has been observed that in many cases, two-dimensional simulation schemes can grasp the majority of the physical processes of solute transport and reduce the simulation complexity and calculation costs, compared with threedimensional simulations. In addition, in the previous study, we found that when the cementation degree increases, the velocity probability distribution of fluid in 2D media and 3D media and its change trend are similar [28,29]. Therefore, this study performed two-dimensional simulations at the pore scale for the purpose of exploring the solute dilution processes in porous media with different cementation degrees.…”
Section: Methodsmentioning
confidence: 89%
“…In many laboratory and field scale studies [12][13][14][15], results show that the solute transport followed the non-Fickian transport. By fitting the experimentally measured or directly simulated breakthrough curves of solute plumes with continuous-time random walk (CTRW) models, some studies [16][17][18] indicated a strong link between the non-Fickian transport and heterogeneity of porous media. The varied geometry of pore channels and the cementation of solid grains are very common in natural solids, resulting in the heterogeneity of porous media.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that the characteristics of pore channels such as connectivity or pore particle distribution could affect the flow field and solute transport processes [19,20]. The evolution of solute mixing in porous media with different degrees of heterogeneity is caused by the changes in pore channel geometry and solid grains due to the cementation of porous media [17]. However, little attention has been focused on this problem until now.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing numerical and experimental evidences have demonstrated that a realistic solute transport process exhibits behavior that deviates systematically from the predictions of the ADE (Hou et al, 2018; Scheven et al, 2005; Wirner et al, 2014). For example, by fitting measured breakthrough curves (BTCs) with the ADE, Levy and Berkowitz (2003) have shown that the measured BTCs are distinctly different from the sigmoid BTCs predicted by the ADE.…”
mentioning
confidence: 99%
“…There are many studies that have demonstrated that the CTRW model can provide a convincing description of the time behavior of the transport process over a wide range of cases (Berkowitz et al, 2000; Bijeljic et al, 2013; Xiong et al, 2006). Unfortunately, little validation has been conducted for the application of CTRW to describe the time behavior of solute migration in cemented porous media (Hou et al, 2018). In this study, the cementation degree is measured quantitatively by the ratio of the cemented solid volume (the volume occupied by multiple solid grains) to the total solid volume.…”
mentioning
confidence: 99%